Criminal Policy of The Exploitation of Flying Fish Eggs in Outheast Maluku Waters - Yanti Amelia Lewerissa; Abd Asis (JURNAL BELO, 2022)
Illegal retrieval of flying fish eggs in the waters of Southeast Maluku has a negative impact on sustainable capture fisheries activities. This study aims to analyze the criminal policy of using flying fish eggs in the waters of Southeast Maluku. The research method used is normative juridical research. Assisted with a social legal approach. The data sources used are secondary data consisting of primary legal materials, secondary legal materials and tertiary legal materials. The data was collected by means of a literature study, then analyzed qualitatively. The exploitation of flying fish eggs carried out by fishermen from the provinces of South Sulawesi and Southeast Sulawesi is illegal. There has been a memorandum of understanding (MoU) between the Maluku government and the South Sulawesi government but there has been no follow-up in the form of a cooperation agreement (PKS) between the two regional governments. As for the Regional Government of Southeast Sulawesi, there is no MoU and there is also no PKS with the Regional Government of Maluku. Likewise with the Regent and Mayor Regulations which essentially prohibit fishermen from outside from entering the surrounding area, due to the Covid-19 pandemic. There needs to be a policy to overcome the exploitation of flying fish eggs. Either by using penal means (criminal law) or by using non-penal means (non-criminal law). There needs to be community participation through Pokmaswas, outreach to the community, and guidance to fishermen who use flying fish eggs.